The First Experience of Clinical Practice on Psychology Students’ Imaginary - Gallo-Belluzzo, Sueli Regina; Corbett, Elisa; Aiello-Vaisberg, Tania Maria Jose (Paidéia (Ribeirão Preto), 2013)
Considering the academic development of the psychologist as a complex process which articulates the transmission of scientific knowledge and changes in imaginative activity, we psychoanalytically investigate the collective imaginary of Psychology students regarding the first clinical consultation. We conducted a group interview with 52 undergraduate students, using the Thematic Story-Drawing Procedure as a way to open a dialogical field. The material obtained, through the psychoanalytical method, resulted in the creation/gathering of four affective-emotional meaning fields: “I came, I saw and I conquered”, “I know that I (do not) know”, “I survived and I will save” and “I am and I do”, from which we see an emotionally immature imaginary about the meeting with the patient, since students are more self-centered than concerned with the patient. The overall situation indicates the need for care regarding student academic development, in order to encourage a more mature approach toward the suffering of the other.